Evidence-based practice implementation in healthcare in China: a living scoping review - Junqiang Zhao; Wenhui Bai; Qian Zhang; Yujie Su; Jinfang Wang; Xiaoning Du; Yajing Zhou; Chang Kong; Yanbing Qing; Shaohua Gong; Meiqi Meng; Changyun Wei; et al. (Elsevier, 2022)
Summary: Background: Evidence-based practice (EBP) implementation plays a crucial role in bridging the knowledge-action gaps and reducing health inequities. Little is known about its development in China. This study aims to provide an overview of the EBP implementation research progress in healthcare in China and identify gaps for future studies. Methods: We conducted a scoping review following the Joanna Briggs Institute scoping review methodology and the Cochrane Collaboration's guidance on living reviews. We performed a literature search in four Chinese databases (i.e., China National Knowledge Infrastructure, Wan Fang Database, The VIP Database, and China Biology Medicine) and three English databases (i.e., Ovid MEDLINE, the Cumulative Index to Nursing and Allied Health Literature, and EMBASE), Google scholar, and Baidu scholar from 1996 to 2021. We included EBP implementation studies conducted in healthcare settings in China and were published in Chinese and English literature. The search will be run on a regular basis to monitor the development of new literature and determine when to update the review. Findings: Of the 11,276 records identified, we finally included 309 papers. The publications were on a sharp rise since 2013 and were predominantly from the nursing field (292/309, 94.50%). The commonly researched areas were symptom management (75/309, 24.27%), tube care (46/309, 14.89%), perioperative care (43/309, 13.92%), and fundamental care (43/309, 13.92%). Joanna Briggs Institute model was the most frequently used model to guide the implementation process (92/159, 59.75%). A median number of 8 people often comprised an implementation team, with 113 studies (36.57%) taking a multidisciplinary approach. 204 studies reported utilizing audit criteria to assist evaluation of evidence implementation rate with diversified methods measuring the criteria. Lack of knowledge, skills, and resources, and incomplete procedures or pathways were top barriers impeding EBP implementation. Leadership support was considered the most common facilitator. Education and training were the most frequently described implementation strategies for healthcare professionals and patients. Optimizing workflows and developing evaluation tools were the primary strategies adopted by organizations. 291 studies measured patient outcomes and 174 studies measured healthcare professional outcomes. Interpretation: To our knowledge, this scoping review is the first one to systematically examine the EBP implementation research progress in healthcare in China. Based on this review, we identified contributions that Chinese EBP implementation research made to the global community, and provided eight recommendations for Chinese researchers in conducting implementation studies in the future. Funding: None.